العولمة وسيادة الدولة في ظل القانون الدولي العام. "تحليل الاليات والاثار واستراتيجيات موجهتها". (Comprehensive Journal of Science, 2025)
This research addresses the topic of Globalization and State Sovereignty in Public International Law: An Analysis of Mechanisms, Impacts, and Confrontation Strategies.It presents the conceptual framework of globalization and sovereignty, highlighting the variations in their definitions among jurists and scholars. The study analyzes the mechanisms through which globalization affects state sovereignty and examines the multidimensional impacts—political, economic, security, and cultural—resulting from these mechanisms.Furthermore, the research discusses the future of sovereignty in the era of globalization, emphasizing the necessity for states to strategically adapt to the challenges posed by globalization.Finally, the study aims to provide recommendations that contribute to strengthening national sovereignty within the framework of globalization.
Keywords: Globalization, National Sovereignty, Public International Law, Dimensions of Globalization, Global Impacts, International Strategies.